Improving students’ achievement trought role play method in legal education learning (pkn) at the fifth grade students’ in sd negeri no. 16 sungai putih kecamatan bayang - Ernayeti Ernayeti (Fakultas Sastra Universitas Ekasakti, 2018)
The purpose of this study was to describe how can the design, implementation and learning outcomes in learning civics by using role playing.The research was conducted on half Odd.The research that the authors do is a classroom action research (PTK) using a qualitative and quantitative approach. The research was conducted based on observations in fifth grade of semester of Odd, SD Negeri No. 16 Sungai Putih kecamatan Bayang, when delivering materials still dominate Civics teachers teaching and students learning not active in other words, learning is still centered on the teacher. This resulted in low student learning outcomes and not as expected. To improve student learning achievement on the learning of Civics was held a classroom action research. Cycle I was held two meetings and cycle II was held one meeting with 4 stages of planning, implementation, observation and reflection. With the research subjects were fifth grade students of Elementary School No. 16 Sungai Putih Kecamatan Bayang. The results of data analysis showed that the use of Role Play method can improve learning outcomes of students in elementary school civics class. This can be seen from (1) Planning in cycle I 78, 57% and increased to 89,28% in cycle II, (2) Implementation from teacher aspect in cycle I 70,5% and increased to 90% in cycle II, then The students' aspect in cycle I 69% increased to 88% in cycle II, (3) Student learning outcomes in cycle I increased from 66 average value increased to 81,43 in cycle II. Thus Role Playing proved that the method can improve learning achievement of students in civics at fifth grade students’ in SD Negeri No. 16 Sungai Putih Kecamatan Bayang.